Da metáfora à substância: redes sociais, redes migratórias e migração nacional e internacional em Valadares e Ipatinga - Weber Soares (2002)
This work aims at analyzing the connections among the international emigration, the international migratory network and the internal migratory networks, considering two complementary analytic perspectives of social network: the Ptolemaic and the Copernican. The analytic incursion in the domain of these connections tries to shed light to the specific cases of Valadares (MG) and Ipatinga (MG), which have similar traditions of international migration, although presenting opposite economic performance: relative economic stagnation in Valadares and economic growth in Ipatinga. The adoption of the theoretical panel on the Social Network Analysis (SNA) allows to state that the transformation of the international migration in mass phenomenon in Valadares and Ipatinga is due to the constitution of an international migratory network that is supported by existent social networks and gives rise to other networks in connection with the "shared principle" of migrating. This network, originated in Valadares, enlarges its scope to incorporate the neighboring areas. The first intend to check the internal consistency of this assertive was to apply direct and indirect demographic techniques to the census data of 1970, of 1980 and of 1991 to evaluate the role of the international emigration in the demographic dynamics of the micro-region of both Valadares and Ipatinga. The singularities of the international emigration of Valadares are revealed through the connections between the international emigration and the Valadares international migratory network, the elements of that network, and the structural conditions that explain the migration to other countries. The analysis of the internal population flows of both Valadares and Ipatinga with the remaining of the Brazilian territory, in the periods 1970/1980 and 1981/1991, based on the Ptolemaic perspective of the Social Network Analysis, allows to point out the migratory flows that were more intensely linked to these two micro-regions. In addition, it puts in evidence the nexus between the internal migration and the international migration. Finally, the analytic step that considers the population flows immigrants and emigrants of last migratory stage of the periods 1970/1980 and 1981/1991, among 91 Brazilian micro-regions, according to the Copernican perspective of the social networks, identifies the micro-regions that are more connected by the internal migration, those that are less connected, those that are more central, those that give more stability to the reticular structures and those that occupy similar positions.